2013
DOI: 10.7717/peerj.11
|View full text |Cite
|
Sign up to set email alerts
|

Assessing insect responses to climate change: What are we testing for? Where should we be heading?

Abstract: To understand how researchers are tackling globally important issues, it is crucial to identify whether current research is comprehensive enough to make substantive predictions about general responses. We examined how research on climate change affecting insects is being assessed, what factors are being tested and the localities of studies, from 1703 papers published between 1985 and August 2012. Most published research (64%) is generated from Europe and North America and being dedicated to core data analysis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
92
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(95 citation statements)
references
References 52 publications
(59 reference statements)
1
92
0
1
Order By: Relevance
“…Only 13 years ago, it was concluded that there was no strong evidence to show that climate change was exerting a demonstrable impact on vector-borne diseases, such as malaria, dengue, leishmaniosis and tick-borne diseases (50). In spite of the large amounts of data being gathered, we are still a long way from knowing whether insects and other organisms are responding and adapting to climate change and if such changes apply widely across taxa, space and time (51). The principal difficulty is the absence of long-term (>50 years) data sets, which means that we lack a strong baseline against which to compare and assess species responses to climate change (5).…”
Section: Climatic Factors and Culicoidesmentioning
confidence: 99%
“…Only 13 years ago, it was concluded that there was no strong evidence to show that climate change was exerting a demonstrable impact on vector-borne diseases, such as malaria, dengue, leishmaniosis and tick-borne diseases (50). In spite of the large amounts of data being gathered, we are still a long way from knowing whether insects and other organisms are responding and adapting to climate change and if such changes apply widely across taxa, space and time (51). The principal difficulty is the absence of long-term (>50 years) data sets, which means that we lack a strong baseline against which to compare and assess species responses to climate change (5).…”
Section: Climatic Factors and Culicoidesmentioning
confidence: 99%
“…Field population peaks, determined by both pheromone trap catches and crop infestation scouting, were observed in the warmer austral summer [19,22,49]. Regardless of the population source, high temperatures were shown to hasten development and thus shorten life cycles in P. xylostella [36,37]. However, temperature may differentially affect organisms, such that different insect pests (hosts) and their associated natural enemies may develop at different rates and thus affect host-prey/parasitoids synchronisation [26,33,50,51].…”
Section: Horticulture and Dbm In Southern Africamentioning
confidence: 99%
“…In SA, temperature is projected to increase by 1-3 • C by 2050 [45][46][47] and its effects are likely to be more pronounced in the drier tropics than the humid subtropics [8,9]. In laboratory experiments, DBM showed activity over a broad temperature range, measured as LLTs and ULTs [36,38]. This may mean that, under the currently projected climate change in SA, DBM pest status is likely to increase, exacerbating already failing management practices [18,25,48].…”
Section: Horticulture and Dbm In Southern Africamentioning
confidence: 99%
“…Within the insects, we target the ants (Family: Formicidae), a ubiquitous and diverse insect group that has received relatively little climate change research (Andrew et al 2013a;Gibb et al 2015), and we do so through an investigation of communities rather than single species. Ant communities have a long history of use as indictors of disturbance (Andersen and Majer 2004;Solar et al 2016) and play crucial roles in ecosystem functioning on all continents except Antarctica; as invertebrate and seed predators, seed dispersers, detritivores, herbivore ''farmers'', in bioturbation and mutualisms, and as a food source for other invertebrates and vertebrates (Lach et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Insect focused climate change research is however scant, especially so in Asia, Africa and Australasia, and in particular where habitats are modified and landscapes are fragmented. Available research has concentrated on changes in abundance and/or distribution shifts of single species due to climate change, most commonly butterflies in Europe (Wilson et al 2007;Felton et al 2009), or insects of concern to primary producers (Andrew et al 2013a).…”
Section: Introductionmentioning
confidence: 99%